Good Teaching and Satisfied University Graduates - Krahn, Harvey; Bowlby, Jeffrey W. (Canadian Journal of Higher Education, 2017)
This paper examines the extent to which students' evaluations of university teaching and classroom dynamics contribute to overall satisfaction with their university experience. Data were collected from 1453 graduates of the University of Alberta who completed questionnaires follow- ing the 1993 spring Convocation. A multi-item index measuring students' evaluations of university teaching and classroom experiences was employed as the central predictor in a multiple regression analysis of overall satisfaction with the university experience. Positive perceptions of teaching had a strong impact on satisfaction, controlling on gender, age, faculty of enrollment, GPA, prior postsecondary experience, assessments of skill development, satisfaction with university learning-related resources, and several other control variables. The findings highlight the continued importance of efforts to encourage good teaching in universities.